New species and stages description of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Northeast Brazil - Nascimento, Stênio R. S.; Lima, Lucas R. C.; Mariano, Rodolfo; Azevêdo, Carlos A. S. (Zootaxa, 2020)
The genus Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) has 15 described species, three of them recorded from Brazil: Traverella bradleyi (Needham & Murphy, 1924), T. insolita Nascimento & Salles, 2013 and T. maranhensis Nascimento, Lima & Azevedo, 2019. In the present work, we provide the description of a new species to the genus based on nymphs and male imagos and provide description of the nymphal stage of T. maranhensis, based on collections from Maranhão State. Additionally, an updated key of male imagos is provided.